1990
DOI: 10.1111/j.1399-0039.1990.tb01829.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐DP incompatibilities induce significant proliferation in primary mixed lymphocyte cultures in HLA‐A, ‐B, ‐DR and ‐DQ compatible individuals: Implications for allogeneic bone marrow transplantation

Abstract: The major part of the proliferative response in primary mixed lymphocyte cultures (MLC) is caused by HLA-DRB1 incompatibilities. In DRB1-matched pairs the proliferation induced by HLA-DRB3, -DQ and -DP mismatches may be unmasked. In most previous studies the influence of HLA-DP incompatibilities in primary MLC has been investigated in homozygous typing cells representing only a few Dw specificities. We were interested in determining the stimulatory capacity of isolated HLA-DP mismatches, ascertained by RFLP an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
2

Year Published

1991
1991
2013
2013

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 36 publications
0
14
0
2
Order By: Relevance
“…Traditional methods for typing HLA-DP gene products include the primed lymphocyte test, a modified mixed lymphocyte culture method in which 6 alloantigens could be distinguished. 28,29 The extensive sequence polymorphism of this locus mandated the use of modern DNA-based methods to uncover undetected donor-recipient disparity (http:// www.ebi.ac.uk/imgt/hla/stats.html). 12 In addition, it was shown that while much of the MHC displays strong positive linkage disequilibrium (LD; where certain alleles are seen together at a higher frequency than would be predicted by chance), LD weakens between HLA-DQB1 and HLA-DPB1, resulting in a high incidence of mismatching for DPB1 5,14,30 and a low chance of identifying DPB1-matched donors even when there is matching for other HLA genes.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional methods for typing HLA-DP gene products include the primed lymphocyte test, a modified mixed lymphocyte culture method in which 6 alloantigens could be distinguished. 28,29 The extensive sequence polymorphism of this locus mandated the use of modern DNA-based methods to uncover undetected donor-recipient disparity (http:// www.ebi.ac.uk/imgt/hla/stats.html). 12 In addition, it was shown that while much of the MHC displays strong positive linkage disequilibrium (LD; where certain alleles are seen together at a higher frequency than would be predicted by chance), LD weakens between HLA-DQB1 and HLA-DPB1, resulting in a high incidence of mismatching for DPB1 5,14,30 and a low chance of identifying DPB1-matched donors even when there is matching for other HLA genes.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Interestingly, Rutten and colleagues observed high levels of cytokine production by CD4 ϩ T cells in response also to autologous DP molecules presumably presenting minor histocompatibility antigens, 5 suggesting that the HeLa cell transfectants expressing DP but not other class II antigens used in their experiments may not quantify physiologic frequencies of alloreactive T helper cells, which increase substantially with the number of mismatched HLA-DP alloantigens in classical in vitro assays. 9,10 Here, we have quantified the frequency of alloreactive CD4 ϩ T cells responding to permissive or nonpermissive TCE3 or TCE4 DP mismatches, in classical MLRs between peripheral blood mononuclear cells (PBMCs) of responder (R)-stimulator (S) pairs matched for 10/10 of the non-DPB1 alleles. When S presented both a permissive and a nonpermissive mismatch, the percentage of responding CD4 ϩ T cells was more than 10-fold higher against the nonpermissive (DPB1*09:01, 10.65%) compared with the permissive mismatch (DPB1*04:02, 0.88%; Figure 1A), and this result was highly reproducible in 3 independent experiments (data not shown).…”
Section: Significantly Higher Frequencies Of Alloreactive Cd4 ؉ T Celmentioning
confidence: 99%
“…Akraba olmayan grupta MLC testi yapılan vakalarda pozitif sonuçların az olmasının sebebini de kabul edilen yüksek RRI değerlerinden kaynaklanmış olabileceğini belirtmişlerdir. Ayrı-ca bu çalışmada iki DP uyumsuzluğu olan hasta verici çiftlerin-de, tek DP uyumsuzluğuna göre RRI değerlerinde daha fazla artış olduğu görülmüştür (8). Vakamızdaki DP uyumsuz akraba çiftin MLC sonucunun pozitif bulunması Olerup ve ark.…”
Section: Discussionunclassified